Chloride‐Induced Aufbau of Perchlorinated Cyclohexasilanes from Si2Cl6: A Mechanistic Scenario. Issue 30 (25th April 2014) - Tillmann, Jan; Meyer, Lioba; Schweizer, Julia I.; Bolte, Michael; Lerner, Hans‐Wolfram; Wagner, Matthias; Holthausen, Max C.
Abstract A surprisingly simple preparative procedure, addition of Si2Cl6 to a solution of [nBu4N]Cl in CH2Cl2, leads to the formation of the chloride‐complexed cyclic dianions [Si6Cl12⋅2Cl]2−, [(SiCl3)Si6Cl11⋅2Cl]2−, or [1, y‐(SiCl3)2Si6Cl10⋅2Cl]2− (y=1, 3, 4), depending on the stoichiometric ratio of the reactants and the reaction temperature (25–85 °C). Below −40 °C the open‐chain oligosilane chloride adducts [Si3Cl9]−, [Si3Cl10]2−, [Si4Cl11]−, and [Si6Cl15]− are formed, again depending on the reaction conditions chosen. All species were characterized by X‐ray crystallography. The underlying reaction mechanism is elucidated by DFT calculations. It incorporates all experimental findings and involves a few key elementary steps: 1) chloride‐induced liberation of SiCl3− or higher silanides, 2) their addition to neutral silanes yielding larger oligosilane chloride adducts, 3) dimerization of larger silanides to (substituted) cyclohexasilane dichloride adducts with inverse sandwich structure.